Electoral bias and policy choice: Theory and evidence - Timothy Besley; Ian Preston (Institute for Fiscal Studies (IFS), 2007)
This paper develops an approach to studying how bias in favor of one party due to the pattern of electoral districting affects policy choice. We tie a commonly used measure of electoral bias to the theory of party competition and show how this affects party strategy in theory. The usefulness of the approach is illustrated using data on local government in England. The results suggest that reducing electoral bias leads parties to moderate their policies.
Keywords: 330; Wahlverhalten; Parteiprogramm; Großbritannien; Meinung; Politische Willensbildung; Ökonometrisches Modell